THE USE OF CARTOGRAPHIC MATTER FROM OPEN SOURCES FOR MASS ASSESSMENT AT THE PRE-STAGE STUDY OF HYDROPOWER CONSTRUCTION - A. A. Tesalovsky (Модернизация, инновация, развитие, 2016)
In the article the possibility of planning and cartographic materials and supplies to remote sensing of the Earth, which can get them open sources for mass valuation of land at the pre-stage study on developing a multi-purpose reservoirs on the plains and plateaus. Particular attention is given to the use of the service "Public cadastral map', available on the portal of the Federal Service for State Registration, Cadastre and Cartography: advantages and disadvantages of the use of undeveloped and sparsely populated areas of service information. Clarified what objects other than those required by regulatory and technical documents and regulations can be obtained by using the public cadastral map using its various functions: cadastral division maps, raster maps Russian and available on a portal of Earth Remote Sensing Data. In the article it is assumed that the accuracy of the image contour of the situation and the relief map material from open sources corresponds to map scale is larger than 1: 100 000 with the height of the relief section of not less than 20 meters. Mass assessment is based on the possibility of placing some or all of the seven species of water potential in the waters of hydroelectric complex. Potential benefits of each of the water users, attributable to the land plot is set on the basis of the cadastral value of land corresponding to each type of water. The area used by each of the water users, established in accordance with its requirements to the bottom topography, the provisions of water and nature protection legislation. Justification is made on the basis of the calculation of measurement error plot area used by water users in their economic activity, taking into account the errors in the image of the contour of the situation on these maps. It was found that the error introduced by cartographic materials used in certain methods of mass estimation of cost of land area, reserved for the construction of multi-purpose reservoirs does not exceed 0.6-1.3%. In accordance with the provisions on the determination of the estimated cost of construction of unique structures allowable error should be no more than 10%.